Vietnam - Wright, David K. (Chicago : Childrens Press, 1989)
Discusses the geography, history, people, economy, and customs of Vietnam.
Includes index.
Booklist.
School Library Journal.
6.7
4-9.
5-8
Keywords: Vietnam -- Juvenile literature; Vietnam; Vietnam